CASE REPORT: CHRONIC RHINITIS AND TOXOCARIOSIS IN A 9-MONTH-OLD DOMESTIC CAT - Muhamad Abdul Shidiq; Sri Kayati Widyastuti; I Gusti Made Krisna Erawan (Buletin Veteriner Udayana, 2025)
Chronic rhinitis in cats is a disease associated with inflammation of the nasal cavity. A 9-month-old male domestic cat named Oyen, weighing 2.5 kg, was brought to the Veterinary Internal Medicine Laboratory, Faculty of Veterinary Medicine, Udayana University, complaining of yellow discharge from both nostrils and sneezing for approximately 4 months. Clinical examination revealed stridor during breathing, mucopurulent discharge from both nostrils, and sneezing. A nasal swab cytology examination revealed rod-shaped bacteria, which were confirmed by bacterial isolation and identification, indicating the growth of Bacillus sp. and Staphylococcus sp. Routine hematology examination showed an increase in lymphocytes and a decrease in granulocytes. Fecal examination using the native method showed the presence of Toxocara sp. eggs. Based on these examinations, the cat was diagnosed with chronic rhinitis and toxocariosis. The cat was given therapy consisting of the antibiotic Cefixime (10 mg/kg body weight; every 12 hours; orally (PO)), the anti-inflammatory corticosteroid Methylprednisolone (2 mg/cat; every 12 hours; PO), the mucolytic Bromhexine HCl (1 mg/kg body weight; every 12 hours; PO), and the vitamin Livron B-Plex (1 tablet/cat; every 12 hours; PO). Toxocariasis was treated with Combantrin® syrup (5 mg/kg). After 7 days of treatment, the cat showed improvement, with a reduction in nasal discharge and a reduction in sneezing frequency. The owner is advised to take the other two cats to the vet for immediate treatment to prevent them from transmitting the disease to each other, to maintain a clean environment, and to keep the animals confined during the treatment period.